Switchable release of bone morphogenetic protein from thermoresponsive poly(NIPAM-co-DMAEMA)/cellulose sulfate particle coatings - Müller, Martin; Grab, Anna Luise; Cavalcanti-Adam, Elisabetta A. (Polymers, 2018)
Thermoresponsive coatings of poly(N-isopropylacrylamide-co-DMAEMA)/cellulose sulfate (PNIPAM-DMAEMA/CS) complexes are reported eluting bone-morphogenetic-protein-2 (BMP-2) on demand relevant for implant assisted local bone healing. PNIPAM-DMAEMA/CS dispersions contained colloid particles with hydrodynamic radii RH = 170-288 nm at T = 25 °C shrinking to RH = 74-103 nm at T = 60 °C. Obviously, PNIPAM-DMAEMA/CS undergoes volume phase transition (VPT) analogously to pure PNIPAM, when critical VPT temperature (VPTT) is exceeded. Temperature dependent turbidity measurements revealed broad VPT and VPTT 47 °C for PNIPAM-DMAEMA/CS colloid dispersions at pH = 7.0. FTIR spectroscopy on thermoresponsive PNIPAM-DMAEMA/CS particle coatings at germanium model substrates under HEPES buffer indicated both wet-adhesiveness and VPT behavior based on diagnostic band intensity increases with temperature. From respective temperature courses empirical VPTT ≈ 42 °C for PNIPAM-DMAEMA/CS coatings at pH = 7.0 were found, which were comparable to VPTT found for respective dispersions. Finally, the PNIPAM-DMAEMA/CS coatings were loaded with BMP-2 and model protein papain (PAP). Time dependent FTIR spectroscopic measurements showed, that for T = 37 °C there was a relative protein release of ≈ 30% for PAP and ≈ 10% for BMP-2 after 24 h, which did not increase further. Heating to T = 42 °C for PAP and to 47 °C for BMP-2 further secondary protein release of ≈ 20% after 24 h was found, respectively, interesting for clinical applications. BMP-2 eluted even at 47 °C was found to be still biologically active.